Four new Pinnularia Ehrenberg (Bacillariophyta, Pinnulariaceae) species from Amazonian black water (Tupé Lake, Amazonas State, Brazil) - Pereira, Andreia Cavalcante; Torgan, Lezilda Carvalho; Melo, Sergio (Phytotaxa, 2014)
Tupé Lake belongs to one of the Sustainable Development Reserves in the Negro River Basin, Amazonas State, Brazil. It connects to the Negro river by a channel, so its level varies according to the floods of the river. The water has low pH (< 5), low conductivity (< 7.60 µS.cm-1) and high temperature (> 28.5ºC). During a taxonomic study of the genus Pinnularia, four new species are described: P. manausensis Pereira & Torgan, P. nelsonii Pereira & Torgan, P. tupensis Pereira, Melo & Torgan and P. walkerae Pereira & Torgan. The study was based on samples taken during October and December 2003 (low waters) and September 2008 (falling), including samples of plankton and sediment. The morphology of the species is compared to closely related (similar) taxa. Detailed valve structures of some species are documented with scanning electron microscopy.